Obstetrics and Gynecology Fellowship Interview Preferences [22I]. Issue 1 (May 2017) - Barnard, Emily; Byrnes, Jenifer; Occhino, John A.
Abstract : INTRODUCTION: The number of applicants to Obstetrics and Gynecology subspecialty fellowships is projected to increase; however, it is known that the interview process is taxing for both applicants and the programs they attend. Concerns include excessive time away from work, cost, lack of coordination for regional travel, and overlapping interview dates. Little is known about applicant preferences for interviewing. METHODS: An e-mail link to a survey designed using web-based tool SurveyMonkey was sent to all residency directors for distribution to fourth year residents at ACGME-accredited Obstetrics and Gynecology programs in the United States. RESULTS: A total of 190 residents responded, 138 of whom applied to fellowship in 2016. Applicants were predominantly female (73.6%), Caucasian (78.3%), married (76.7%), and without children (74.4%). Most (81.3%) were from an academic program. Applicants attended a mean of 10.9 interviews; the most common reason to cancel was conflict with another interview (72.3%). Saturday was the most preferred interview day (46.7%). The majority of applicants preferred half-day interviews (93.2%), and 61.0% preferred an 0800 start to earlier or later times. A pre-interview dinner was favored (64.4%) with work restraints being the largest barrier to attendance. Personal days granted for interviews varied by program from zero (16.1%) to greater than 11 (25.0%). Vacation and unpaid leave were utilized by 56.5% and 9.0% respectively. CONCLUSION: Interviewing for fellowship is a burdensome process, but it could be improved by implementing regional coordination, shorter interview days and weekend interview dates. Gathering information from applicants and fellowship directors can help further streamline the process.